IMITATION IN LINGUISTICS - Dilrabo Khasanovna Saidakhmetova (Journals Park Publishing, 2023)
Calque in linguistics is the borrowing of foreign words, phrases by a literal translation of the corresponding language unit, as well as the result of these borrowings: words, expressions and phrases. Linguistics, lexicology and translation studies are engaged in the study of tracing paper. Tracing papers arise as a reaction of native speakers to a sharp increase in the number of direct borrowings of foreign words that are being introduced into everyday life and science - in different historical periods.
Keywords: Russian language, communication, information transfer, borrowed words, interlingual communication, borrowing, borrowing.